2–18ghz Radar Pencari Arah - Hussin, Mohd Ridhuan (Universiti Sains Malaysia, 2006)
This report presents the design of radar direction finder which will be use to detect the receiving signal in the frequency range of 2GHz to 18GHz. This range of frequency is commonly use by the military for their operations. This system is design with the combination of several parts such as receiver antenna, low noise amplifier circuit, mixer down converter circuit, varactor tuned oscillator circuit, band pass filter circuit, RF to DC voltage converter circuit, amplifier circuit, analog to digital converter (ADC) circuit, digital to analog converter (DAC) circuit and finally the 8051 microcontroller trainer board. In this system, the receiver antenna that will be use is from the antipodal vivaldi antenna type. Its need exactly eight identical antenna to make this direction finder system to works well. Each design and simulation done in this project is using the software called HPADS. The control and process unit for this system is done by the 8051 microcontroller.